WORK CULTURE, WORK FAMILY CONFLICT, AGE, AND EMPLOYEE ENGAGEMENT IN SHARIA FINANCIAL INSTITUTIONS - Hikmah Endraswati; Melis, Melis (CV. Era Digital Nusantara, 2022)
Every institution has their own culture which are differentiate them with the others. Work culture is a set of attitude, belief, values, and regulations which are determine how the employee interacts with the others. Furthermore, work family conflict is a conflict which is happened because of individual experiences incompatible between work and family roles. Employee who has this conflict cannot balance the role in work and family. Age in this research refers to millennial and non-millennial age. Millennial age is age under 40 and non-millennial age is age upper 40. Finally, employee engagement is a dedication and spirit of the employee to the organization. The purpose of this study is to examine the effect of work culture and work family conflict to employee engagement with age as a moderating variable. The sample of this research is 150 employees in sharia financial services of Yogyakarta and area around Yogyakarta. The data analysis technique which is used in this research is multiple regression with split sample in age. Age is divided into millennial and non-millennial age. The results show that work culture has a positive effect on employee engagement in both of groups. Additionally, work family conflict has positive effect on employee engagement in non-millennial age and work family conflict has negative effect on employee engagement in millennial age.